Pelvic Floor Dysfunction after Prolonged Second Stage of Labor [12A]. (May 2018) - Gimovsky, Alexis; Amero, Molly; Phillips, Jaclyn; Levine, Jordan; Berghella, Vincenzo
Abstract : INTRODUCTION: To evaluate whether extending the length of labor in nulliparas with prolonged second stage (PSS) affects the incidence of self-reported pelvic floor dysfunction. METHODS: Planned follow up survey to our randomized controlled trial of PSS using the Pelvic Floor Distress Inventory- 20 (PFDI-20): composed of the Pelvic Organ Prolapse Distress Inventory (POPDI-6), Colorectal-Anal Distress Inventory (CRADI-8) and Urinary Distress Inventory (UDI-6). Primary outcome: PFDI-20 summary score. Secondary outcomes: POPDI-6, CRADI-8, UDI-6 scores. Inclusion criteria: nulliparas, singleton gestation, 36.0 - 41.6 weeks, PSS. Women surveyed were previously enrolled in a study that assigned them randomly to extended labor (EL)- at least 1 additional hour in the 2nd stage, or to usual labor (UL)- expedited delivery via cesarean/operative vaginal delivery at the diagnosis of PSS. Women were surveyed at 12 - 36 months postpartum. RESULTS: Survey response rate was 43.6% (34/78). Maternal demographics were similar between groups. PFDI-20 summary score was 13.8 ± 23.3 in the EL and 13.1 ± 20.9 in the UL group (p = 0.9). POPDI-6 was 1.2 ± 2.9 in the EL group and 2.7 ± 6.4 in the UL group (p = 0.4). CRADI- 8 was 0.8 ± 2.8 in the EL group and 2.1 ± 4.0 in the UL group (p = 0.6). UDI- 6 was 11.8 ± 21.1 in the EL group and 8.3 ± 14.5 in the UL group (p = 0.6). CONCLUSION: Extending the length of labor in nulliparas with singleton gestation and PSS did not have an impact on PFDI-20 scores at 12-36 months postpartum.